2014
DOI: 10.1111/pcmr.12210
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in regulatory DNA elements: the case of OCA2 transcriptional regulation

Abstract: Summary Mutations within the OCA2 gene or the complete absence of the OCA2 protein leads to oculocutaneous albinism type 2. The OCA2 protein plays a central role in melanosome biogenesis, and it is a strong determinant of the eumelanin content in melanocytes. Transcript levels of the OCA2 gene are strongly correlated with pigmentation intensities. Recent studies demonstrated that the transcriptional level of OCA2 is to a large extent determined by the noncoding SNP rs12913832 located 21.5 kb upstream of the OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 87 publications
1
29
0
2
Order By: Relevance
“…Several reports suggest that certain SNP can increase the expression of their mRNA transcripts or proteins (Wojnowski and Brockmoller, 2004;Visser et al, 2014). Even for heterozygous individuals it has been reported that SNP could alter the expression of ABCG2 (Kobayashi et al, 2005).…”
Section: Short Communicationmentioning
confidence: 98%
“…Several reports suggest that certain SNP can increase the expression of their mRNA transcripts or proteins (Wojnowski and Brockmoller, 2004;Visser et al, 2014). Even for heterozygous individuals it has been reported that SNP could alter the expression of ABCG2 (Kobayashi et al, 2005).…”
Section: Short Communicationmentioning
confidence: 98%
“…Several cave forms (Pachon, Molino, and Micos) have accumulated different loss‐of‐function mutations in the ocular and albinism‐2 ( Oca2 ) gene, resulting in abnormal melanin synthesis (Protas et al, ; Gross and Wilkens, ). Although the exact function of Oca2 is unclear, it is the most commonly mutated gene associated with albinism in humans (Visser et al, ). Other cavefish populations, including some that exhibit albinism, also have accumulated mutations in the melanocortin‐1 receptor ( Mc1r ) gene resulting in a reduction in the number of melanophores and melanin pigmentation (Gross et al, ).…”
Section: Troglomorphy In Cavefishes and Salamandersmentioning
confidence: 99%
“…OCA type 5, type 6, and type 7 are three recently identified types of nonsyndromic OCA. Type 5 has been mapped to the human chromosome 4q24, which is a novel locus for nonsyndromic OCA (Kamaraj et al, 2014;Visser, Kayser, Grosveld, & Palstra, 2014), and type 6 and type 7 are respectively caused by mutations in SLC24A5 and C10orf11 (Wei et al, 2013). In Chinese Han population, comprehensive molecular analysis has revealed the spectral distribution of Chinese OCA: the three commonest types are OCA type 1, OCA type 2, and OCA type 4 with the prevalence of 64.3%, 11.7%, and 15.6%, respectively (Wei, Zang, Zhang, Yang, & Li, 2015).…”
Section: Introductionmentioning
confidence: 99%